2016
DOI: 10.1038/cddis.2016.407
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of ASPP2 improves hepatocellular carcinoma cells survival via promoting BECN1-dependent autophagy initiation

Abstract: Autophagy is an important catabolic process, which sustains intracellular homeostasis and lengthens cell survival under stress. Here we identify the ankyrin-repeat-containing, SH3-domain-containing, and proline-rich region-containing protein 2 (ASPP2), a haploinsufficient tumor suppressor, as a molecular regulator of starvation-induced autophagy in hepatocellular carcinoma (HCC). ASPP2 expression is associated with an autophagic response upon nutrient deprivation and downregulation of ASPP2 facilitates autopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Another important mechanism of cell death in cancer cells in response to chemotherapy is autophagy, which takes places in the lysosome by self-degrading intracellular proteins and organelles. It triggers cell death in the absence of apoptotic regulators, but in the presence of important autophagy-regulated genes such as BECN1 [7] and ATG5 [8]. In this review, we primarily confine our discussion to apoptotic cell death and autophagic cell death caused by natural chemotherapeutic agents in the context of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Another important mechanism of cell death in cancer cells in response to chemotherapy is autophagy, which takes places in the lysosome by self-degrading intracellular proteins and organelles. It triggers cell death in the absence of apoptotic regulators, but in the presence of important autophagy-regulated genes such as BECN1 [7] and ATG5 [8]. In this review, we primarily confine our discussion to apoptotic cell death and autophagic cell death caused by natural chemotherapeutic agents in the context of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that the different background of HCC cell lines is a critical factor that affects the function of ASPP2-induced autophagy on inducing or inhibiting apoptosis. Previous studies demonstrated that ASPP2 is an autophagy inhibitor that impairs the formation of the autophagosome membrane by interacting with Atg5 (10,11). However, a previous study also demonstrated that ASPP2 could induce autophagy development by increasing CHOP expression.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, we demonstrated that ASPP2 expression was significantly decreased in ESCC and was associated with TNM stage, histological differentiation and lymph node As a tumor suppressor and an activator of p53 family, the expression of ASPP2 is often reduced in malignant tumors and it is involved in apoptosis in cancer cells [15,16]. For example, Song B et al analyzed the expression level of ASPP2 in pancreatic cancer tissue samples with qRT-PCR, Western Blot and immunohistochemistry staining.…”
Section: Discussionmentioning
confidence: 97%
“…As a tumor suppressor and an activator of p53 family, the expression of ASPP2 is often reduced in malignant tumors and it is involved in apoptosis in cancer cells [15,16]. For example, Song B et al.…”
Section: Discussionmentioning
confidence: 99%